Traditional Chinese medicine (TCM)-what is myth and what is the state of evidence today? - Hempen, Carl-Hermann; Hummelsberger, Josef (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2020)
Traditional Chinese medicine (TCM) is the most comprehensive and widely practiced system of medicine in the world.Originally, TCM appeared in our Western context as an unfathomable mythological doctrine. Once the linguistic barriers had been overcome, it became possible to understand and apply the terminological and physiological concepts, the method of diagnosis, and the clinical findings.Since the NIH consensus conference in 1998, our understanding of TCM has been the subject of methodologically robust studies. We now have evidence of the efficacy and effectiveness of acupuncture beyond its use in pain therapy and allergy treatment. Thanks to fMRI studies, among others, we also have a better understanding of the mechanisms underlying acupuncture.Meta-analyses and studies also confirm the efficacy of Chinese medicinal drugs and remedies in some fields, yet there is still extensive need for further research. But opportunities are also emerging for new medicines and prescriptions for (accompanying) treatments of infections, autoimmune diseases, cancer, metabolic illnesses, dermatological disorders, and gastrointestinal diseases.To enable further evaluation of TCM, but also to ensure an integrative, critical application in the practice of TCM, it is vital for doctors to have thorough training. Further institutionalisation is necessary to provide orientation and patient safety.The days of regarding TCM as some kind of mysticism are indeed long over and it can offer real opportunities for better patient care. In many fields, there is increasing evidence of TCM's effectiveness, yet further comprehensive research is essential. This should be encouraged unconditionally.